Agreement between cervical cancer screening methods in Nepal: A cross-sectional study - Paneru, Rupa; Adhikari, Shree Prasad; Vaidya, Sapana Amatya; Poudel, Sandesh; Paneru, Bandana; paudel, Pratiksha; Shrestha, Sabin; Acharya, Achyut (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: Cervical cancer is a leading health concern in Nepal, prompting the utilization of various screening methods like visual inspection with acetic acid (VIA), human papillomavirus deoxyribonucleic acid testing (HPV DNA), and liquid-based cytology (LBC). Yet, understanding their comparative performance remains subject of research. Hence, this study aimed to assess the agreement levels among VIA, HPV DNA, and LBC. Methods: A cross-sectional survey was conducted involving 68 women aged 30 to 60 years visiting Paropakar Maternity and Women’s Hospital. Each woman underwent LBC, VIA, and HPV DNA testing during their outpatient visits after receiving written informed consent and taking detailed history. Those with positive results from any test underwent cervical biopsy and managed. Data were analyzed using SPSS version 22.0 to calculate agreement percentages and kappa values, which range from -1 to 1, with 1 indicating perfect agreement. Results: The result showed 7% positivity rate for visual inspection with acetic acid, 5.9% for Human papillomavirus deoxyribonucleic acid testing, and 4.4% for liquid-based cytology. Agreement between VIA and LBC stood at 85.3%, with a low Kappa value of 0.0047, VIA and HPV DNA testing agreed at 83.8%, with a Kappa value of 0.0064. Conversely, LBC and HPV DNA testing showed higher agreement at 95.6%, with a moderate Kappa value of 0.55. Conclusions: While there is some agreement between LBC and HPV testing, the preliminary findings suggest a difference between agreement and Kappa values between VIA and LBC, as well as VIA and HPV testing, which requires confirmation in a larger, powered study.